2001
DOI: 10.1046/j.1365-2818.2001.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage of water in environmental scanning electron microscopy

Abstract: SummarySpecimen damage from the electron beam poses a considerable problem with electron microscopy. This damage is particularly acute in environmental scanning electron microscopy (ESEM) for two reasons. Firstly, owing to its ability to stabilise insulating and hydrated specimens, ESEM lends itself to polymeric and biological materials that are typically highly beam-sensitive. Secondly, water acts as a source of small, highly mobile free radicals, which accelerate specimen degradation. By taking the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 17 publications
(40 reference statements)
0
98
0
Order By: Relevance
“…However, application of a coating of course requires that the specimen be in the solid state (either dried or frozen)-a step that was avoided for the purposes of this investigation. Finally, it should be noted that although there is a possibility of radiation damage to uncoated specimens in the water vapor environment of an ESEM (Jenkins and Donald 1997, Kitching and Donald 1998, Royall et al 2001, this was not found to be significant under the conditions used for this work.…”
Section: Resultsmentioning
confidence: 84%
“…However, application of a coating of course requires that the specimen be in the solid state (either dried or frozen)-a step that was avoided for the purposes of this investigation. Finally, it should be noted that although there is a possibility of radiation damage to uncoated specimens in the water vapor environment of an ESEM (Jenkins and Donald 1997, Kitching and Donald 1998, Royall et al 2001, this was not found to be significant under the conditions used for this work.…”
Section: Resultsmentioning
confidence: 84%
“…For further details concerning radiation damage of water and of wet samples see e.g. Kitching and Donald (1998) or Royall et al (2001). To minimize radiation the acceleration voltage was kept low (8 kV) and the beam exposure time short.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the beam damage to yeast cells occurred significantly faster under the low vacuum mode than the high vacuum. The result is expected as the water molecules present under the low vacuum mode can accelerate specimen degradation (Royall et al 2001;Kitching and Donald 1998). …”
Section: Calibration Of the Moving Speed Of The Nanomanipulatormentioning
confidence: 99%